PERTUMBUHAN CACING TANAH ( Lumbricus rubellus ) DENGAN PEMBERIAN PAKAN BUATAN UNTUK MENDUKUNG PROSES PEMBELAJARAN PADA KONSEP PERTUMBUHAN DAN PERKEMBANGAN INVERTEBRATA - Elya Febrita '; Darmadi ' '; Endro Siswanto ' (Biogenesis, 2015)
Research has been conducted in order to determine the growth of the earthworm (Lumbricus rubellus) with artificial food and utilization of research results to support the learning process on the concept of growth and development of invertebrates. This research was conducted at the Natural Laboratory of Education and Teacher Training University of Riau in April to June 2013. This study used a completely randomized design with 9 treatments and 3 replications. The material used is the earthworm (Lumbricus rubellus) as much as 270 worm with averaged biomass and body length. Organic materials as artificial feed (P1) tofu, (P2) kakawatan grass, (P3) chicken manure, (P4) cow manure, (P5) tofu + chicken manure, (P6) + kakawatan grass + tofu, (P7) chicken manure and kakawatangrass (P8) + cow manure + tofu. Parameters measured were the length and biomass of earthworm for 60 days after planting (at the beginning and end of the research). Proponent parameters measured were pH of soil, temperature of soil and moisture. Data were analyzed using analysis of variance (ANOVA) followed by DMRT (Duncan Multiple Range Test) at the level of 5 %. The results showed increase length and biomass of earthworm (Lumbricus rubellus) is highest at (P4)treatment (cow manure) which is 0.214 g/tail, long worms present in the (P2) treatment (kakawatan grass) which is 4.99 cm and the lowest on all parameters is the (P0) treatment (no treatment). The results of the research can be used to support the learning process in the form of Student Worksheet (LKS).Keywords : Lumbricus rubellus, Growth, Artificial Feeding, LKS